The Ubiquitin Ligase RNF34 Participates in the Peripheral Quality Control of CFTR (RNF34 Role in CFTR PeriQC) - Taniguchi, Shogo; Ito, Yukiko; Kiritani, Hibiki; Maruo, Asuka; Sakai, Ryohei; Ono, Yuji; Fukuda, Ryosuke; Okiyoneda, Tsukasa (Frontiers in Molecular Biosciences, 2022)
The peripheral protein quality control (periQC) system eliminates conformationally defective CFTR, including ∆F508-CFTR, from the plasma membrane (PM) and limits the efficacy of pharmacological therapy for cystic fibrosis (CF). The ubiquitin (Ub) ligase RFFL is responsible for the chaperone-independent ubiquitination and lysosomal degradation of CFTR in the periQC. Here, we report that the Ub ligase RNF34 participates in the CFTR periQC in parallel to RFFL. An in vitro study reveals that RNF34 directly recognizes the CFTR NBD1 and selectively promotes the ubiquitination of unfolded proteins. RNF34 was localized in the cytoplasm and endosomes, where RFFL was equally colocalized. RNF34 ablation increased the PM density as well as the mature form of ∆F508-CFTR rescued at low temperatures. RFFL ablation, with the exception of RNF34 ablation, increased the functional PM expression of ∆F508-CFTR upon a triple-combination of CFTR modulators (Trikafta) treatment by inhibiting the K63-linked polyubiquitination. Interestingly, simultaneous ablation of RNF34 and RFFL dramatically increased the functional PM ∆F508-CFTR by inhibiting the ubiquitination in the post-Golgi compartments. The CFTR-NLuc assay demonstrates that simultaneous ablation of RNF34 and RFFL dramatically inhibit the degradation of mature ∆F508-CFTR after Trikafta treatment. Therefore, these results suggest that RNF34 plays a crucial role in the CFTR periQC, especially when there is insufficient RFFL. We propose that simultaneous inhibition of RFFL and RNF34 may improve the efficacy of CFTR modulators.